Determinasi Struktur Modal pada Perusahaan Manufaktur Sub Sektor Perkebunan : Peran Return on Equity dan Current Ratio - Seflidiana Roza; Ida Nirwana; Mutia Susanti (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This investigation aims to explore how Return on Equity (ROE) and Current Ratio affect Capital Structure in manufacturing firms operating in the plantation segment listed on the Indonesia Stock Exchange. The analysis included 21 companies chosen through a purposive sampling method, covering the timeframe from 2021 to 2023. By employing multiple linear regression analysis, it was determined that both ROE and Current Ratio have an effect on Capital Structure, represented by the regression formula Y = 1.081 + 0.914X1 - 0.230X2 + c. The initial t-test results indicate that the ROE variable (X1) does not have a significant impact on Capital Structure, as its t-value of │1.887│ is below the t-table value of │1.999│, and the significance level stands at 0.067 (which exceeds 0.05). Consequently, the alternative hypothesis (Ha) is dismissed while the null hypothesis (Ho) is accepted. Likewise, the Current Ratio variable (X2) demonstrated no notable impact, highlighted by a t-value of │-1.625│ < │1.999│ and a significance level of 0.113, leading to a similar rejection of Ha and acceptance of Ho. The F-test results illustrate that ROE and Current Ratio do not have a significant combined effect on Capital Structure, with an F-value of │2.185│ falling short of the F-table value of 3.150, in addition to a significance value of 0.127 (greater than 0.05). Thus, it can be concluded that when looked at together, ROE and Current Ratio do not significantly influence Capital Structure. On the other hand, a separate F-test examining Business Risk and Asset Structure revealed a substantial joint effect on Capital Structure, with an F-value of │32.694│ exceeding the F-table value of 3.090, alongside a significance level of 0.000 (which is less than 0.05), hence supporting Ha. Moreover, the coefficient of determination (R²) was calculated at 0.106, indicating that ROE and Current Ratio account for 10.6% of the variation in Capital Structure, while the remaining 89.4% can be attributed to additional factors not examined in this research.